Earth As It Is - Maher, Jan (Book collections on Project MUSE., 2017)
"Charlene (aka Charlie) Bader is one of society's least understood people--a heterosexual cross-dressing man. It's the 1930s in Texas when Charlie comes of age with urges he has struggled with since childhood and does not understand. After his new bride finds him wearing her own sexy lingerie and leaves him in disgust, he tries to move on. His efforts lead him to Chicago, where he stumbles on a community of cross-dressers and begins to attend their secret soirees. When Pearl Harbor is bombed, he volunteers for the army, serving as a dentist and trying once again to leave his obsession with soft clothes behind. Instead, his wartime experiences combined with the Army's faulty record-keeping lead to his reappearance in the small town of Heaven, Indiana, as Charlene. There, Charlene opens a beauty shop where Heaven's women safely share their stories and secrets as she shampoos, clips, curls, and combs their hair. Charlene deftly manages to keep her own story hidden and her sexual desires quiet until she falls in love with a female customer and her life begins to change."--